The Pair Lion Motif in Shiva Temple of Medieval Bengal: Its Source and Evaluation - Islam, Sk. Zohirul (American International Journal of Social Science Research, 2018)
Lions, particularly male lions, have been an important symbol for thousands of years and appear as a theme in cultures across Europe, Asia, and Africa. The cultural significance of stucco pair lion motif in Shiva temples of Bengal and relates with various types of representation of the same motif found in others. The pair Lion used as stucco (Jora Shiva Temple, Muroli, Jessore district). Shiva is the braver among the all God and Goddesses in Hindu religion during the early period and still. Thus we have found many Shiva temple build in Bengal (present West Bengal(Paschimbango) and Bangladesh). This article try to analyses about how the pair lion motif is depicting of the Shiva temple and what is the relation between Shiva and lion under Mythology and Purana. Shiva is the second most important male deity of Hindu. The usual Shiva –lingam’s which were mainly worshipped in the temples and under trees or in an open space. We would have tried to decipher about Pair Lion Motif decoration of 18th – 19th century Shiva temple of Bangladesh. Those would have to help the history of evaluation of stylized art waves is coming out by its  decoration  motif with ritual, beliefs and faith of Bengal society. We may look at the artistic tradition of lion sculptures those are widely found from different parts of west Bengal and Bangladesh.